Inhibition of Mineralization of Urinary Stone Forming Minerals by Some Hills Area Fruit Juice - N. A. Mohamed Farook; G. A. Seyed Dameem; N. M. I. Alhaji; R. Sathiya; J. Muniyandi; S. Sangeetha; J. Muniyandi. (E-Journal of Chemistry)
Some hills area fruit, viz., star fruit, butter fruit, seetha fruit, and watermelon have been investigated as inhibitors in the mineralization of urinary stone forming minerals, viz., calcium phosphate, oxalate and carbonate. Inhibition efficiency has been studied in different models. Increased intake of the experimental fruits would be helpful in urinary stone proppylaxis. Most of the inhibitors have found effectively inhibit calcium phosphate and oxalate precipitation.